2020
DOI: 10.3389/fmicb.2020.576438
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nutrients From Anaerobically Digested Swine Wastewater Using an Intermittent Cycle Extended Aeration System

Abstract: Swine wastewater contains high concentrations of organic compounds, nutrients (nitrogen and phosphorus), heavy metals, and residual antibiotics, amongst others, that have negative impacts on the water environment. The main aim of this work was to remove nutrients from anaerobically digested swine wastewater using an intermittent cycle extended aeration system (ICEAS). The effects of operational parameters such as cycle time, organic loading rate, C/N ratio, and aeration/mixing ratio on the pollutant removal ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Khalaf et al (2021) compared the use of conventional activated sludge systems and SBRs for the treatment of dairy wastewater; the findings reported SBRs to be more effective in treatment of dairy wastewater and reported removal efficiencies ranging from 85-90%, the maximum removal reported lower than that in this study of >99% [28]. Dan et al (2020) tested the performance of an Intermittent Cycle Extended Aeration System (ICEAS) and compared to conventional SBR treatment for treatment of digested swine effluent, the findings of this study found that the intermittent aeration strategy employed facilitated higher treatment performance than that of conventional treatment, with removal rates for NH 4 -N reported similar to those in this study, i.e., up to 97% reported under certain operational conditions [36].…”
Section: Overview Of Contaminant Removal Throughout the Studysupporting
confidence: 66%
“…Khalaf et al (2021) compared the use of conventional activated sludge systems and SBRs for the treatment of dairy wastewater; the findings reported SBRs to be more effective in treatment of dairy wastewater and reported removal efficiencies ranging from 85-90%, the maximum removal reported lower than that in this study of >99% [28]. Dan et al (2020) tested the performance of an Intermittent Cycle Extended Aeration System (ICEAS) and compared to conventional SBR treatment for treatment of digested swine effluent, the findings of this study found that the intermittent aeration strategy employed facilitated higher treatment performance than that of conventional treatment, with removal rates for NH 4 -N reported similar to those in this study, i.e., up to 97% reported under certain operational conditions [36].…”
Section: Overview Of Contaminant Removal Throughout the Studysupporting
confidence: 66%
“…Improper disposal of these wastewaters can cause groundwater contamination, odor problems, health hazards including the release of harmful pathogens and hormones, and eutrophication resulting in harmful algal blooms and ‘dead zones’ in aquatic ecosystems [ 5 , [19] , [20] , [21] , [22] ]. Though this untreated wastewater is detrimental to the environment, it can be viewed as a resource if the nutrients are appropriately utilized [ 23 ]. Therefore, mitigating these wastes and producing value-added commodities in the same process is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Digested swine wastewater has high concentrations of nutrients (N and P) but lacks readily biodegradable COD (rb-COD). In digested swine wastewater, the concentrations of COD, total nitrogen (TN), and total phosphorus (TP) are in the range of 887 to 3286 mg/L, 176 to 1379 mg/L, and 22 to 415 mg/L, respectively [7][8][9][10][11][12]. Because digested swine wastewater has a low carbon/nitrogen (C/N) mass ratio and lacks rbCOD, denitrifiers compete with phosphorus-accumulating organisms (PAOs) for rbCOD [13].…”
Section: Introductionmentioning
confidence: 99%